Positron Emission Tomography in Animal Models of Tauopathies - Cao, Lei; Kong, Yanyan; Ji, Bin; Ren, Yutong; Guan, Yihui; Ni, Ruiqing (Frontiers in Aging Neuroscience, 2022)
The microtubule-associated protein tau plays an important role in Alzheimer’s disease, Frontotemporal dementia and tauopathy related neurological disorders.Tau contributes to the development of neurotoxicity, inflammation, and neurodegeneration causing cognitive deficits in tauopathy diseases. It synergically interact with amyloid-beta in Alzheimer’s disease leading to detrimental consequence. Thus tau has been an important target for therapeutics development for Alzheimer disease and other primary tauopathy diseases. Tauopathy animal models recapitulating the tauopathy such as transgenic, knock-in mouse and rat models have been developed and greatly facilitated the understanding of disease mechanisms. The advance in positron emission tomography (PET) and imaging tracers have enabled non-invasive detection of the accumulation and spread of tau, the associated neuroinflammation, microglia activation, metabolic, neurotransmitter receptor alterations in disease animal models. In vivo microPET studies on mouse or rat models of tauopathy have provided significant insights into the phenotypes, and time course of pathophysiology of these models and the monitoring of treatment targeting at tau. In this review, we discuss the utilities of PET and recently-developed tracers for evaluating the pathophysiology in tauopathy animal models. We point out the outstanding challenges and propose future outlook in visualizing tau-related pathophysiological changes in brain of tauopathy disease animals model.